Alterações hemodinâmicas, cardíacas e vasculares induzidas pelo treinamento físico combinado em ratos espontaneamente hipertensos tratados ou não com Dexametasona - Tardelli, Lidieli Pazin (Universidade Federal de São Carlos, 2021)
Arterial hypertension (HT) is usually accompanied by neural, cardiac and vascular alterations. Dexamethasone (DEX)-induced hypertension is observed in normotensive rats, but little is known about the effects of DEX of arterial stiffness and vessel remodeling on normotensive and spontaneously hypertensive rats (SHR). Combined training (aerobic exercise on alternate days with resistance exercise) has been recommended as a preventive and non-pharmacological treatment for HT, but the mechanisms induced by combined training to reduce HT are not totally known. Therefore, the aim of this study was to evaluate the effects of DEX treatment on arterial pressure (AP) and arterial stiffening of Wistar and SHR, as well as the effects of combined training on the hemodynamics of SHR treated or not with DEX. Wistar and SHR were treated with DEX (50µg/kg s.c.) for 14 days. SHR were submitted to combined training for 74 days and were treated with DEX during the last 14 days. Echocardiographic parameters, AP, pulse wave velocity (PWV), as well as histological and morphometric analyses of the heart and aorta, carotid and femoral arteries were performed. The results show that control SHR (SHRCT) had higher AP then control Wistar (WCT), associated with autonomic imbalance to the heart. Echocardiographic changes in SHRCT (vs WCT) were suggestive of cardiac remodeling: higher relative wall thickness (RWT, +28%) and left ventricle mass index (LVMI, +26%) and lower LV systolic diameter (LVSD, -19%) and LV diastolic diameter (LVDD, -10%), with slightly systolic dysfunction and preserved systolic function. In addition, SHRCT had lower myocardial capillary density and similar collagen deposition area. PWV was higher in SHRCT due to higher aortic collagen deposition. DEX-treated Wistar rats presented higher AP (~23%) and autonomic imbalance to the heart. DEX did not change cardiac structure in Wistar, but PWV (+21%) and aortic collagen deposition area (+21%) were higher compared with control. However, DEX did not change AP, autonomic balance to the heart or arterial stiffness in SHR, but reduced RWT and LV collagen deposition area (-12% vs SHRCT). On the other hand, combined training reduced AP (~18%), PWV (-20%) in SHR (SHRTCT), which was associated with better autonomic balance to the heart, reduced myocardial collagen deposition (-18%), as well as lower collagen deposition aorta (-23%), carotid (-35%) and femoral (-14%). In addition, combined training completely blocked any increase of AP or estimated PWV induced by DEX in SHR, as it does in normotensive rats. No effect of DEX treatment or combined training on vessel remodeling was observed in arteries. In conclusion, the results suggest a differential effect of dexamethasone on arterial stiffness, myocardial remodeling, and AP between Wistar and SHR. On the other hand, combined training proved to be an important strategy to reduce AP and arterial stiffness in SHR, and these lower responses were maintained regardless of DEX treatment.
Hemodynamic, cardiac and vascular changes induced by combined exercise training in spontaneously hypertensive rats treated or not with Dexamethasone
Keywords: Velocidade de onda de pulso; Treinamento aeróbio; Treinamento resistido; Deposição colágeno; Hipertensão; Artérias; Pulse wave velocity; Aerobic training; Resistance training; Collagen deposition; Hypertension; Arteries; CIENCIAS BIOLOGICAS::FISIOLOGIA